2022
DOI: 10.3389/fpsyg.2021.765530
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Resilience and Posttraumatic Growth Among the Primary Caregivers of Children With Developmental Disabilities: The Mediating Role of Positive Coping Style and Self-Efficacy

Abstract: This study was conducted to investigate the relationship between posttraumatic growth (PTG), resilience, positive coping style, and self-efficacy among the primary caregivers of children with developmental disorders in Chongqing, China. A total of 198 primary caregivers (parents and grandparents) aged from 22 to 66 years old (M = 35.55, SD = 9.16), including 155 females (78.3%) and 43 males (21.7%), were enrolled. The Posttraumatic Growth Inventory, Connor-Davidson Resilience Scale-10, Simplified Coping Style … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
5
0
1
Order By: Relevance
“…Similarly, the investigation of caregivers (parents and grandparents) of children with developmental disabilities revealed that a positive coping style was positively correlated with PTG. 21 Disengagement coping, characterized as avoidance and denial, is more related to the definition of negative coping style in this study. Disengagement coping was found to be positively correlated with PTG among parents of children who underwent hematopoietic stem cell transplantation, 15 which contradicted our results.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Similarly, the investigation of caregivers (parents and grandparents) of children with developmental disabilities revealed that a positive coping style was positively correlated with PTG. 21 Disengagement coping, characterized as avoidance and denial, is more related to the definition of negative coping style in this study. Disengagement coping was found to be positively correlated with PTG among parents of children who underwent hematopoietic stem cell transplantation, 15 which contradicted our results.…”
Section: Discussionmentioning
confidence: 60%
“…The PTG of parents of children with developmental disabilities did not differ depending on the children's diagnosis. 21 In parents of children with special needs (children with physical and developmental impairments), there were no significant differences in PTG according to the child's type of diagnosis. 40 Versus e significant at P = .021.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It can buffer psychological stress well and the better self-efficacy is more likely to exhibit the more positive behaviors, such as self-management (Nott et al, 2021), better job performance (Downes et al, 2021), and a positive coping style (Wang and Zhang, 2021;Wu et al, 2021). Therefore, individuals with good self-efficacy tend to adopt a positive coping style in the process of event handling (Lu et al, 2021). Given that self-efficacy is an important determinant of the choice of positive coping style, it is feasible to hypothesize that recruits' psychological stress has a negative effect on self-efficacy, and self-efficacy has a positive effect on positive coping style and a negative effect on negative coping style.…”
Section: Research Theory and Hypothesismentioning
confidence: 99%